Pengembangan Bahan Ajar E-Komik Menggunakan Web Pixton Pada Tema 3 Materi Sistem Pencernaan Manusia - Hanifa, Syifa Astriani; Novita, Lina; Gani, Resyi A. (Jurnal Sains dan Teknologi, 2023)
E-comic teaching materials are one of the teacher's tools in the learning process to convey material to students by combining the use of technology and story illustrations as an effort to innovate in the development of teaching materials. This study aims to develop e-comic teaching materials on theme 3 of human digestive system material, using the Research and Development (R&D) method and the ADDIE model (Analysis, Design, Development, Implementation, and Evaluation). This research was conducted at SDN Pajajaran Bogor class V which consisted of 26 students as respondents. The results of this study indicate that the development of e-comic teaching material products gets very feasible criteria, based on the results of validator assessments and student responses. This is based on the percentage results of media experts 94.66%, linguists 97.33%, material experts 96% and the results of the student response questionnaire 93.07%. Based on this, it can be concluded that the e-comic teaching material product using pixton web on theme 3 of human digestive system material developed is suitable for use as teaching material.